Project Management Efficiency Strategy for Public Safety Center (PSC) Building in Probolinggo Regency - Lucky Hendra Saputra; Andi Patriadi; Sajiyo Sajiyo (Journal of World Science, 2025)
This research examines the efficiency of managing the construction of the Public Safety Center (PSC) building in Probolinggo Regency. Effective management ensures the project meets its timeline, budget, and quality goals. We used a method called Earned Value Analysis to track progress and identify potential issues early on. Key indicators like the Cost Performance Index (CPI) and Schedule Performance Index (SPI) helped us understand how well the project was performing in terms of cost and schedule. The research revealed challenges such as material delays and labor shortages, which impacted the project's efficiency. By analyzing these issues, we propose solutions to improve project planning and execution, focusing on better resource allocation and scheduling. The findings offer valuable insights for future construction projects, helping to minimize delays and overspending. This research emphasizes the importance of identifying project performance issues promptly to ensure overall success. The recommendations can guide improvements in construction project management, ensuring projects are completed on time, within budget, and to the required quality standards.